A Case of Isolated Cardiac Hydatid Cyst that Mimics Lymphoproliferative Malignancy. Issue 6 (3rd December 2014) - Yildiz, Cenk Eray; Sinan, Ümit Yaşar; Yildiz, Ahmet; Çetin, Gürkan; Küçükoğlu, Serdar
<x xml:space="preserve">Abstract</x> Cardiac cystic echinococcosis is a rare parasitic infestation caused by Echinococcus granulosus larvae and it composes 0.5–2% of all human cystic echinococcosis cases. The left ventricle is the most common affected area followed by right ventricle, interventricular septum, left atrium, right atrium, and interatrial septum. The diagnosis is difficult because of nonspecific clinical and radiographic findings. We present a case of isolated apical cardiac cystic echinococcosis mimicking lymphoproliferative disease.